2020
DOI: 10.1002/sstr.202000018
|View full text |Cite
|
Sign up to set email alerts
|

Drug Targeting via Platelet Membrane–Coated Nanoparticles

Abstract: Platelets exhibit distinct surface moieties responsible for modulating their adhesion to various disease‐relevant substrates involving vascular damage, immune evasion, and pathogen interactions. Such broad biointerfacing capabilities of platelets have inspired the development of platelet‐mimicking drug carriers that preferentially target drug payloads to disease sites for enhanced therapeutic efficacy. Among these carriers, platelet membrane–coated nanoparticles (denoted “PNPs”) made by cloaking synthetic subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 134 publications
(161 reference statements)
2
101
0
Order By: Relevance
“…[7,8] Recently there is accumulating research interests focused on treat-to-target approaches against RA, including active interference of IL-1 pathway and other selective strategies. [9][10][11][12][13] Particularly, the treatment of blocking IL-1 is regarded as an effective targeted therapy for IL-1-directed inflammatory diseases, in contrast to attenuated performance of the non-specific antiinflammatory drugs. [13] Although the medication of IL-1 receptor antagonist (IL1ra) has been approved by the US Food and Drug Administration (FDA), it is reported that the protein IL1ra therapeutic and derivatives show short half-life from a few minutes to 1-4 h. [14][15][16] It therefore requires frequent dosage administration as high as 1-2 times per day, which greatly decreases patient compliance and results in higher expenses.…”
mentioning
confidence: 99%
“…[7,8] Recently there is accumulating research interests focused on treat-to-target approaches against RA, including active interference of IL-1 pathway and other selective strategies. [9][10][11][12][13] Particularly, the treatment of blocking IL-1 is regarded as an effective targeted therapy for IL-1-directed inflammatory diseases, in contrast to attenuated performance of the non-specific antiinflammatory drugs. [13] Although the medication of IL-1 receptor antagonist (IL1ra) has been approved by the US Food and Drug Administration (FDA), it is reported that the protein IL1ra therapeutic and derivatives show short half-life from a few minutes to 1-4 h. [14][15][16] It therefore requires frequent dosage administration as high as 1-2 times per day, which greatly decreases patient compliance and results in higher expenses.…”
mentioning
confidence: 99%
“…18,19 In short, those platelet-mimicking systems are shielded from the body's immune responses and possess platelet-like binding properties by keeping the platelet adhesion molecules, without causing side effects such as blood clotting and inflammation. 20 Thus, devoid of cytokines, biomimetic platelets-derived nanovesicles can provide a collagen-targeting platform without platelets activation and thrombosis. 14,[17][18][19][20] Inspired by these findings, herein we developed a novel imaging modality to detect PF via biomimetic platelets, namely PVD (platelets-derived nanovesicles labeled with dye).…”
Section: Introductionmentioning
confidence: 99%
“…[32] Certain nanostructures are valuable tools for delivering vaccine components and initiating immune responses, as they provide the opportunity to package the immune activator (adjuvant) and target (antigen) with precise structural control over the placement, orientation, and chemical connectivity of each component, resulting in synergistic immune responses. Indeed, such structures advance therapeutic development, as they allow one to both: 1) manipulate and deliver immunologically active components to target sites, [33][34][35][36][37][38][39][40] and 2) program the pharmacokinetics and codelivery of these compounds. [41][42][43][44][45][46][47] Spherical nucleic acids (SNAs) are nanoscale architectures particularly well suited for immune modulation due to their modularity, tunability, and facile synthesis from chemical building blocks.…”
Section: Introductionmentioning
confidence: 99%